Photodiode performance and infrared light sensing capabilities of quaternary Cu2ZnSnS4 chalcogenide - Al-Sehemi, Abdullah G.; Karabulut, Abdulkerim; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2022)
In this study, quaternary Cu2ZnSnS4 chalcogenide nanocrystal compound prepared by hydrothermal method was coated on Si with the help of spin coating technique to be used as the interfacial layer. SEM and EDX analyzes were performed to investigate the morphological and structural properties of the coated film. In order to determine the optical properties, IR and UV-Vis measurements were made and it was determined that the absorption properties of the material were good in the visible and infrared region, and the optical band gap value was found to be 1.49 eV. In addition, photoelectrical measurements (current-voltage and photo-transient) were performed and evaluated under both solar and infrared lights. As a result of these measurements, it was determined that the photoresponse value gave better results in the measurements made under sunlight. The calculated ideality factor (barrier height) values in the light of the data obtained were found to be 5.087 (0.456 eV), 6.422 (0.449 eV) and 7.789 (0.443 eV) under dark, solar light and infrared light conditions, respectively. As seen from the results, the ideality factor value in the measurements made under solar light is lower than the measurements made under infrared, but the barrier height value is higher. In addition, capacitance-time measurements were performed depending on the light intensity and the produced device showed photocapacitive properties for both light sources. In addition to these measurements, the capacitive properties of the device were also analyzed by taking capacitance and conductivity measurements as a function of frequency and voltage. These measurements revealed that the capacitance and conductivity characteristics of the device are strongly dependent on voltage and frequency. The results of the performed experimental studies confirm that the produced Al/Cu2ZnSnS4/p-Si device is highly sensitive to infrared and sunlight to which it is exposed, and also shows that the produced device configuration can be used in optoelectronic applications.
Keywords: Solar light; Infrared light; Photodiode; Electrical characteristics; Hydrothermal method; Spin coating